Cranial osteology of Cerylinae (Coraciiformes: Alcedinidae) - Calonge-Méndez, Andrés; Höfling, Elizabeth (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2007)
Skull osteology of eight species of Cerylinae Kingfishers (Megaceryle torquata, M. lugubris, M. Alcyon, Ceryle rudis, Chloroceryle amazona, C. americana, C. inda and C. aenea) were compared with other Alcedinidae and representatives of most families of Coraciiformes (Coraciidae, Leptosomidae, Bucerotidae, Upupidae, Todidae, Momotidae and Meropidae) with the purpose of verifying the pattern of the temporal region and the jugal arch. These data were also compared with the information on the bibliography about the Ramphastidae, Picidae, Galbulidae, Capitonidae and Cuculidae. The temporal region with two well delimited fossas, the jugal arch expanded rostrolaterally and quadrate with three saliences on the otical process, are common characters on the Cerylinae kingfishers. Four characters were diagnostic to separate the genera of Cerylinae studied: the dorsal expansion of the orbital process of the lacrimal (absent in Chloroceryle [unavailable in Ceryle rudis], present in Megaceryle); caudal condyle of quadrate (cotylar-shaped in Chloroceryle and Ceryle rudis, condylar-shape in Megaceryle); lateral and caudal cotyles of mandible (non distinct in Chloroceryle and Ceryle rudis, distinct in Megaceryle) and dorsal wall of the caudal fossa of jaw (absent in Chloroceryle and Ceryle rudis, present in Megaceryle).
Keywords: Coraciiformes; Alcedinidae; Skull; Osteology; Systematic